« Coded Voices Speaking from the Walls » : les fresques murales de Belfast dans la prose nord-irlandaise - Stephanie Schwerter (Revue LISA)
Belfast is marked by a number of urban phenomena not to be found in other cities. Due to the residential segregation of the two ethno-religious communities, the city’s topography is shaped by countless boundaries and borders separating Catholic and Protestant areas from each other. The limits between the different territories are indicated by various boundary markers such as peace lines and murals. For the local population, wall paintings have turned into important means of expression. This article explores the function of murals in the following three post-ceasefire novels: Sacrifice of Fools by Ian McDonald, Eureka Street by Robert McLiam Wilson and That Which Was by Glenn Patterson. Drawing on Burton Pike’s opposition of the concepts “real city” and “word city”, I shall engage with the three authors’ different ways of employing existing visual markers in order to distort and mock them in their fictional presentation.